Особенности состояния левого желудочка сердца у больных с ренопаренхиматозной артериальной гипертензией - Н. Ю. Боровкова; Н. Н. Боровков; Ю. А. Хорькина; Е. О. Обухова; Л. А. Бирюкова; А. И. Аршинова (Архивъ внутренней медицины, 2011)
Changing of the structural and functional state of the left ventricle (LV) heart objectively describes his defeat in arterial hypertension (AH). However, the features of changes of LV in patients with renal hypertension currently remain unstudied. The target of our work was to study the structural and functional features of the left ventricle of the heart in patients with renal hypertension without signs of kidney failure.  Echodopplercardiography of structural and functional parameters of left ventricular heart disease was applied in 136 patients with hypertensive form of chronic glomerulonephritis. The study showed that patients with renal hypertension without signs of kidney failure, ranging from grade 2 hypertensive syndrome, LV hypertrophy develops. At the same time in individuals with grade 2 hypertension it is formed by concentric, while grade 3 hypertension, as dilated eccentric. At the same time, with grade 2 and moreover grade 3 items in hypertension systolic LV function was reduced. Diastolic LV dysfunction was diagnosed in all patients with renal hypertension.